ANALISIS MINAT BELAJAR SISWA PADA MATA PELAJARAN FISIKA MENGGUNAKAN BLENDED LEARNING PASCA PEMBELAJARAN TATAP MUKA TERBATAS - Sigiro, Mula; Marbun, Juliaster; Simbolon, Lamtiur Verawati; Sinaga, Gresya Ledy (LPPM Institut Pendidikan Nusantara Global, 2023)
The education in Indonesia is currently experiencing enormous problems due to the spread of Covid 19, therefore the government orders all teachers and lecturers not to do face-to-face learning during the pandemic. Online learning is one solution that teachers and lecturers can do to avoid face-to-face learning. This study aims to see the effectiveness of the success of online learning in the public speaking course at Institut Pendidikan Nusantara Global. This type of research is quantitative research because it will calculate the value obtained by students in online learning during college. Data collection techniques in this study used attendance scores, assignments, midterm exams (UTS), and final semester exams (UAS). The data is then analyzed by accumulating the number of values ​​obtained using the assessment format that has been prepared in the form of Microsoft exel. The results of this study were the graduation rate of all students reached 80.8 with a passing rate reaching 100%. From these results it can be concluded that learning using an online system can be said to be successful.